2022
DOI: 10.1088/1748-9326/ac536d
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting tracks of severe convective storms in West Africa from observations of land surface state

Abstract: In tropical convective climates, where numerical weather prediction of rainfall has high uncertainty, nowcasting provides essential alerts of extreme events several hours ahead. In principle, short-term prediction of intense convective storms could benefit from knowledge of the slowly-evolving land surface state in regions where soil moisture controls surface fluxes. Here we explore how near-real time (NRT) satellite observations of the land surface and convective clouds can be combined to aid early warning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Based on the previous study, Taylor et al . (2022) have developed and shown the potential of using land surface temperature (surface skin temperature) anomalies as soil moisture proxy for nowcasting storms over West Africa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous study, Taylor et al . (2022) have developed and shown the potential of using land surface temperature (surface skin temperature) anomalies as soil moisture proxy for nowcasting storms over West Africa.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Klein and Taylor (2020) found a preference for storms to initiate, intensify and propagate over drier soils (warmer T s ) as compared to the wetter soils. Based on the previous study, Taylor et al (2022) have developed and shown the potential of using land surface temperature (surface skin temperature) anomalies as soil moisture proxy for nowcasting storms over West Africa.…”
Section: Airs Surface Skin and Air Temperaturementioning
confidence: 99%
“…The system could be further improved by including additional meteorological information, either observed or forecast. For example, as land surface temperature (LST) has been shown to constrain the development of convection (Klein & Taylor, 2020; Taylor et al ., 2022), including LST in the nowcasting system could lead to improvements in skill. Including further convective structure properties, such as temperature or size, and larger‐scale atmospheric information related to convective initiation, could also lead to improvements.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For a full list of diagnostic definitions see Clarke and Ansah (2022). Land surface temperature products for Sahel (Taylor et al 2022).…”
Section: Data Availability Statementmentioning
confidence: 99%